The Effect of Sandwich Generation : (Work Psychological, Time Management and Work Commitment) - Salsabilla, Alyssa; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
The study aims to determine the effect of Sandwich Generation (Work Psychology, Time Management and Work Commitment) on the Performance of National University Employees. This research data used primary data in the form of questionnaires to 95 National University respondents. Data analysis techniques using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) program version 22. The results of multiple linear regression analysis show that the variables Work Psychology (X1), Time Management (X2), and Work Commitment (X3) have a positive and significant effect on Employee Performance. The results of this study expect companies to improve compensation, motivation, and time management training that can support employee performance.